ANALISIS DAMPAK PENURUNAN SUBSIDIBAHAN BAKAR MINYAK (BBM) SEKTOR RUMAH TANGGA DI INDONESIA - Yusroni, Nanang (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
This paper tries to examine the impact of household fuel oil subsidy reduction on kerosene demand level during 1978 - 2000. In this research, the writer used two models to analyzed this impact and then determined one of model which explained this impact well. They were Error Correction Model (ECM) and Adjustment Partial Model PAM). The writer used kerosene consumption as a dependent variable, whereas kerosene price, income per capita price, firewood price, charcoal price, and electricity price were independent variables.